Mepolizumab effectiveness in patients with severe eosinophilic asthma and co-presence of bronchiectasis: A real-world retrospective pilot study. (August 2021) - Crimi, Claudia; Campisi, Raffaele; Nolasco, Santi; Cacopardo, Giulia; Intravaia, Rossella; Porto, Morena; Impellizzeri, Pietro; Pelaia, Corrado; Crimi, Nunzio
Abstract: Background: The association of bronchiectasis (BE) in patients with severe eosinophilic asthma (SEA) is quite frequent. Mepolizumab is a well-recognized treatment for SEA; we aim to evaluate its effectiveness in SEA patients with and without BE in real-life. Methods: We performed a single-center retrospective pilot study, including patients with SEA treated with mepolizumab for one year. Asthma control test (ACT), lung function, annual exacerbations rate, oral corticosteroid dosage, FeNO, chronic mucous secretions, blood and sputum eosinophils were recorded at baseline and after 6 and 12 months. Results: we included 32 patients (mean age: 52.3 ± 10, 59% female). 50% showed co-presence of bronchiectasis, (SEA + BE). Significant improvements were found in ACT [(13.8 ± 4.6 to 20.7 ± 4.1, p = 0.0009) and (13 ± 4.8 to 20.7 ± 4.6, p = 0.0003)], annual exacerbations rate [from 7 (4–12) to 0 (0.00–0.75) and from 8 (4–12) to 0 (0–1), p < 0.0001], and blood eosinophils count [748 cells/μL (400–1250) vs. 84 cells/μL (52.5–100), and from 691 cells/μL (405–798) vs. 60 cells/μL (41–105), p < 0.0001] in SEA and SEA + BE group respectively, already after 6 months of treatment. A reduction in daily oral corticosteroids intake at 12 months was shown [from 15 mg (0–25) to 0 mg (0-0), p = 0.003 and from 8.8 mg (0–25) to 0 mg (0-0) (p = 0.01)] in both SEA and SEA + BE, respectively. Similar results were found, comparing SEA + BE patients based on the severity of bronchiectasis. Conclusions: Mepolizumab effectively improves asthma symptoms control, reducing annual exacerbations and corticosteroid intake in all patients with SEA, even in the subgroup with coexisting bronchiectasis, independently of their severity. Highlights: Mepolizumab is effective in the treatment of severe eosinophilic asthma (SEA) in clinical trials and real-life studies. Bronchiectasis is a frequent comorbidity in patients with SEA. Mepolizumab improves symptoms and reduces exacerbations in SEA patients with or without co-presence of bronchiectasis. Mepolizumab showed to be effective in patients with SEA and coexisting bronchiectasis, regardless of their severity. Assessing the co-presence of bronchiectasis may help clinicians select the right biologic for a treatment-specific effect.